Modelling of water adsorption by activated carbons : effects of microporous structure and oxygen content - Abdou Slasli (2004)
The present paper examines the adsorption of water by microporous carbons containing various amounts of surface oxygen and a smaller proportion of basic centres. The modelling of water adsorption for 293 and 310 K, using variable pore size distributions (PSD), confirms that the overall type IV isotherm is the sum of a type I isotherm associated with the specific interactions, and a type V isotherm reflecting the non-specific interactions. The principle of temperature invariance is followed by these isotherms, which indicates that modelling leads to the Dubinin-Astakhov equation. The present approach allows the prediction of water adsorption near room temperature, on the basis of the PSD and the density of oxygen present on the surface area of the micropores. It is assumed, to a first and good approximation, that the pores are slit-shaped and the oxygen distribution is random. (C) 2004 Elsevier Ltd. All rights reserved.